“Signs and Symptoms Tell All”–Pseudoaneurysm as a Cause of Postoperative Bleeding after Orthognathic Surgery–Report of a Case and a Systematic Review of Literature - Kumar, Arun (J Maxillofac Oral Surg, 2020)
PURPOSE: Pseudoaneurysms are one of the rare complications that can be encountered after the orthognathic surgery. We are presenting a new case of pseudoaneurysm of bilateral sphenopalatine artery after Bijaw Surgery in a young male and a systematic review of all the cases in the literature emphasizing on signs and symptoms, epistaxis or bleeding episodes and treatment outcomes. METHODS: A systematic research strategy was planned according to the PRISMA guidelines, and articles were taken from 1986 to September, 2019. A total of 899 articles were selected for screening, out of which only 26 articles met our inclusion and exclusion criteria. These were included in the study for qualitative analysis. RESULTS: Most PAs were associated with Lefort I osteotomy (69.7%), followed by sagittal split osteotomy (24.24%). Average intraoperative blood was 635 ml. Maximum number of episodes of epistaxis/swelling or bleeding occurred in second week. Mean bleeding episodes were 2.58 ± 0.996. The arteries commonly affected were internal maxillary artery (42%), sphenopalatine artery (27.27%), facial artery (15.15%), descending palatine artery (12.12%), internal carotid artery (9.09%) and infraorbital artery (3.03%). Embolization was treatment of choice in 81.81% cases. CONCLUSION: If a patient has recurrent epistaxis or swelling after orthognathic surgery, it is advisable to go for diagnostic imaging like angiography without any delay. In recent times, advanced techniques and expertise are readily available for early diagnosis and management of pseudoaneurysm.